Exploration on the Core Elements of Value Co-creation Driven by AI—Measurement of Consumer Cognitive Attitude Based on Q-Methodology - Zhu, Yi; Wang, Peng; Duan, Wenjie (Frontiers in Psychology, 2022)
Value co-creation (VCC) goes through the stage of co-production, customer experience, service-dominant logic, and service ecosystem. The integration of science and technology has become a key factor to the process of VCC. The rise and application of artificial intelligence (AI) technology has added a new driving force to VCC and began to affect its original practical logic. Based on the consumer perspective, this study uses Q-methodology to measure consumer cognitive attitude toward the use of AI technology in VCC, aiming to explore the key factors that affect VCC. The study found that content quality, information security, efficiency concern, and degree of manipulation have become the important concerns of consumers for VCC under AI integration. Moreover, their different statements have their specific focus and direction. The study demonstrates and analyzes the importance of the four factors and proposes the combination of human and non-human actors (technology and system) to shape the new model of VCC in the future, which is worth further deepening and exploring for academia and enterprises.